Development of an Indonesian Syntax E-Module Using the Kvisoft Flipbook Maker Application - Marlina Agkris Tambunan; Jumaria Sirait; Yanti Arasi Sidabutar; Berliana Sihombing (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to develop an Indonesian Syntax e-module using the Kvisoft Flipbook Maker application that is valid, practical, and interesting as a digital teaching material for students of the Indonesian Language Education Study Program, FKIP, HKBP Nommensen University, Pematangsiantar. The background of this study is based on the dominance of the lecture method and the limitations of interactive digital teaching materials that cause students to have difficulty understanding abstract syntactic concepts. The study uses the Research and Development (R&D) method with a 4-D development model that includes the Define, Design, Develop, and Disseminate stages. Research data were obtained through observation, interviews, student needs questionnaires, expert validation, and practicality tests. The results of the needs analysis showed that 82% of students had difficulty understanding syntax material, 85% stated that learning was still dominated by lecture methods, 90% needed digital teaching materials, and 93% supported the use of interactive e-modules. The product developed was a flipbook-based e-module that combines materials, images, learning videos, exercises, and evaluations in one digital medium. The validation results showed that the e-module obtained a validity level of 89% from material experts and 90% from design experts, categorized as very valid. Meanwhile, the results of the student practicality test reached 91.8%, categorized as very practical. The research findings indicate that the use of the Kvisoft Flipbook Maker-based e-module can increase the attractiveness of learning, facilitate understanding of syntax material, and support student learning independence. Thus, the developed e-module is suitable for use as supporting teaching materials and has the potential to improve the quality of Indonesian Language Syntax learning in higher education